PENGARUH LIKUIDITAS SAHAM, KESEMPATAN BERTUMBUH, DAN PROFITABILITAS TERHADAP RETURN SAHAM (Studi Kasus Pada Sub Sektor Perdagangan Besar Yang Tercatat Di Bursa Efek Indonesia Tahun 2014-2018) - Wahyu Aditya; Herma Wiharno; Siti Nuke Nurfatimah (Jurnal Riset Keuangan dan Akuntansi, 2021)
The purpose of this study is to provide empirical evidence regarding the effect of stock liquidity, investment opportunity set, and profitability on stock returns (Case study on the Large Trade Sub-Sector listed on the Indonesia Stock Exchange 2014-2018). The method used in this research is descriptive and verification methods. The data collection technique is observation not participating. The population is that of the large trade sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018 as many as 36 companies. Samples were taken as many as 30 companies through sampling quotas. The data analysis technique used is panel data regression analysis using Eviews 9 and hypothesis testing is done using the f-test and t-test. Based on the results of the t-test (partial), it shows that stock liquidity has a positive and significant effect on stock returns, investment opportunity set have a positive and insignificant effect on stock returns, profitability has a positive and significant effect on stock returns. Based on the results of the f-test (simultaneous), it shows that stock liquidity, growth opportunities, and profitability simultaneously affect stock returns. Keywords: Stock Liquidity, Investment Opportunity Set, Profitability, Stock   Return